2020
DOI: 10.2478/jvetres-2020-0041
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterisation of African swine fever virus in outbreaks in Ha Nam province, Red River Delta Region of Vietnam, and activity of antimicrobial products against virus infection in contaminated feed

Abstract: AbstractIntroductionAfrican swine fever (ASF) was officially reported in Vietnam in February 2019 and spread across the whole country, affecting all 63 provinces and cities.Material and MethodsIn this study, ASF virus (ASFV) VN/Pig/HaNam/2019 (VN/Pig/HN/19) strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 25 publications
1
11
1
Order By: Relevance
“…Since the first confirmed outbreak of ASFV in China in 2018, the disease has also spread to Mongolia, Vietnam, Cambodia, Hong Kong, Korea (Dem People's Rep. of), Laos, Myanmar, Philippines, Korea (Rep. of), Timor‐Leste, Indonesia, Papua New Guinea and India (Vergne et al., 2020). In Vietnam, the first ASF outbreak in Hung Yen province was confirmed by the Department of Animal Health in February 2019 (Tran, Truong, Dang, et al., 2020; Tran, Truong, Ly, et al., 2020) and an official report was submitted immediately to World Organization of Animal Health (OIE). After seven months, the disease spread to the entire country and approximately six million pigs on infected farms had been culled, suggesting the socio‐economic impact of the disease (Truong et al., 2020).…”
Section: Figurementioning
confidence: 99%
See 4 more Smart Citations
“…Since the first confirmed outbreak of ASFV in China in 2018, the disease has also spread to Mongolia, Vietnam, Cambodia, Hong Kong, Korea (Dem People's Rep. of), Laos, Myanmar, Philippines, Korea (Rep. of), Timor‐Leste, Indonesia, Papua New Guinea and India (Vergne et al., 2020). In Vietnam, the first ASF outbreak in Hung Yen province was confirmed by the Department of Animal Health in February 2019 (Tran, Truong, Dang, et al., 2020; Tran, Truong, Ly, et al., 2020) and an official report was submitted immediately to World Organization of Animal Health (OIE). After seven months, the disease spread to the entire country and approximately six million pigs on infected farms had been culled, suggesting the socio‐economic impact of the disease (Truong et al., 2020).…”
Section: Figurementioning
confidence: 99%
“…Our recent studies indicated that ASFVs circulating in the North Central region and Ha Nam province belonged to the p72 genotype II and CD2v serotype 8 (Tran, Truong, Dang, et al., 2020; Tran, Truong, Ly, et al., 2020). Further analysis of the tandem repeat sequences (TRSs) from ASFV strains in the North Central region showed that it had an IGR II variant with an additional TRS (5′‐GGAATATATA‐3′) between the I73R and I329L genes (Tran et al., 2020a; Tran, Truong, Ly, et al., 2020).…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations